2016
DOI: 10.1177/1708538115598726
|View full text |Cite
|
Sign up to set email alerts
|

The shear stess profile of the pivotal fenestrated endograft at the level of the renal branches: A computational study for complex aortic aneurysms

Abstract: The variant horizontal branch orientation influences the wall shear stress distribution across its length and affects its values only at its transition with the mating vessel. These findings and their potential association with adverse effects deserve further clinical validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…32 Fluid simulation, which may seem essential to simulate biological conditions, was employed in only 1 of 7 FEVAR studies and 4 of 11 PG studies. Probably due to the different nature of both techniques, while different CFD simulation studies to investigate possible devices' behavior can be found regarding FEVAR, [33][34][35][36][37] none of the same nature was found analyzing the PG technique. Although excluded from the present analyses due to the lack of benchtop testing, CFD studies may represent a valuable tool to analyze SG behavior in diverse preselected patients' anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…32 Fluid simulation, which may seem essential to simulate biological conditions, was employed in only 1 of 7 FEVAR studies and 4 of 11 PG studies. Probably due to the different nature of both techniques, while different CFD simulation studies to investigate possible devices' behavior can be found regarding FEVAR, [33][34][35][36][37] none of the same nature was found analyzing the PG technique. Although excluded from the present analyses due to the lack of benchtop testing, CFD studies may represent a valuable tool to analyze SG behavior in diverse preselected patients' anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…The proximal component was exposed to distraction forces of 1.3 to 15.7 N, depending on the inlet cross-sectional area. Georgakarakos et al 12 examined the differences in intraluminal flow dynamics between conventional and pivot fEVAR in a virtual 3-dimensional model. In this estimation of intraluminal wall shear stress, values between 6.3 and 12.48 Pa were measured.…”
Section: Discussionmentioning
confidence: 99%
“…A number of CFD studies have been done on FSGs to evaluate their efficacy for FEVAR. For example, Avrahami et al, 10 Georgakarakos et al, 11 , 12 Kandail et al, 13 , 14 Sun et al, 15 and Sutalo et al, 16 among others, performed CFD simulations on either patient-specific or ideal models of FSGs to shed light on hemodynamic conditions within the fenestrated endoprostheses. With the exception of Sun et al, 15 most of these studies, however, neglected the effect of a flared renal stent.…”
Section: Introductionmentioning
confidence: 99%